臨終關懷——放棄治療的觀念: Withdrawing Treatment and the Care of Termnally Ill Patients - MEN, Xianwu (International Journal of Chinese & Comparative Philosophy of Medicine, 2000)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 當治療有一定效果，卻終止了治療，這種行為對疾病、對病人能夠產生實質性作用，這時才會顯示“放棄治療”的存在意義。如果治療本身存在與否對疾病、對病人並無影響，那麼這種“放棄治療”就是毫無意義的。在臨終關懷中放棄治療的問題是個複雜的問題。當病人處於不可逆轉的臨終狀態時，一般概念下的“治療”對其已毫無意義。所以作者認為，在臨終關懷中不是什麼“放棄治療”的問題，而是應該放棄“治療”這個概念，用“關懷”（care）取代“治療”、“治癒”（cure）的問題。在臨將關懷這門學科中，充分意識到對臨終病人進行治療的無意義性，可以使我們不必徒勞無益地為臨終病人進行所謂“治療”，不必為強調治療而侵犯臨終病人的尊嚴與人格；可以使我們從生命質量論和公益論的角度認識摒棄“治療”的意義，從而有利於臨終關懷學、醫學倫理學和生命倫理學的發展。 Medical treatment is rarely useless in an absolute sense. It is often beneficial and harmful to an extent. This is why withdrawing treatment is a difficult issue. If treatment is entirely futile, then there would not be a painful debate regarding weather treatment should be stopped. This paper explores the complicated issues of withdrawing treatment in the care of terminally ill patients. This paper argues for a shift of concept regarding terminally ill patients. For terminally ill patients, 'cure' or 'medical treatment' in its general medical sense is actually no longer possible in medical practice. Therefore, the real issue involved here is not whether we should give up treatment. It is rather whether we should give up the concept of cure. This paper contends that, for terminally ill patients, since the concept of cure traditionally used is not meaningful to the patients, it should be replaced by the concept of care. In caring the terminally ill patients, the quality of life and the interest of public should be taken into account. We should not violate the patient's dignity or hurt the patient's character by offering aggressove. DOWNLOAD HISTORY | This article has been downloaded 26 times in Digital Commons before migrating into this platform.